A method for preparing a water-based epoxy-modified silicone high-temperature resistant anticorrosive coating
Through the preparation method of water-based epoxy modified silicone high-temperature anti-corrosion coating, the shortcomings of existing coatings in terms of corrosion resistance, mechanical properties and high-temperature resistance are solved, and high-performance coating preparation is realized, suitable for high-temperature and high-corrosion environments Applications under.
Patent Information
- Application Number
- CN202310344682.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-04-03
- Publication Date
- 2025-02-07
- Estimated Expiration
- 2043-04-03
AI Technical Summary
The existing epoxy modified silicone coatings still have shortcomings in corrosion resistance, mechanical properties and high temperature resistance, and cannot meet strict environmental protection and construction safety requirements.
The preparation method of water-based epoxy modified silicone high-temperature anti-corrosion coating is adopted to prepare silicone prepolymer by dropping acidified water to the alkoxysilane monomer, and it is combined with bisphenol A type epoxy resin, solvent and other The additives are mixed and reacted, and finally emulsifier and pH adjuster are added to prepare an aqueous epoxy modified silicone emulsion, and grinded through a mixer to a fineness of ≤30μm.
The produced coatings not only have good corrosion resistance and mechanical properties, but also have excellent high temperature resistance, and are suitable for long-term protection in high-temperature and high-corrosion environments.
Smart Images

Figure BDA0004159164610000081 
Figure BDA0004159164610000091
Abstract
Description
Technical field:
[0001] The invention relates to the field of polymer materials, and in particular to a method for preparing a water-based epoxy-modified organic silicon high-temperature resistant anticorrosive coating. Background technology:
[0002] Silicone resin has always occupied a very important position in the field of high-temperature resistant coatings due to its good heat resistance, water resistance and electrical insulation, but it has many disadvantages such as poor adhesion, organic solvent resistance and corrosion resistance. Epoxy resin is often known for its excellent mechanical properties, corrosion resistance and bonding properties. Therefore, the principle of bonding reaction between the hydroxyl group in the epoxy resin structure and the ethoxy group in the silicone resin can be used to prepare epoxy-modified silicone resin to make up for the shortcomings of single silicone resin in terms of poor adhesion to the substrate and corrosion resistance.
[0003] At present, as people pay more attention to environmental protection and construction safety, the emission requirements of volatile organic compounds (VOC) are becoming increasingly stringent. The development of environmentally friendly coatings is an inevitable choice for my country's coatings industry to achieve product transformation and upgrading and maintain sustainable development. Moreover, although the anti-corrosion performance of epoxy-modified silicone resin coatings in the existing technology has been improved to a certain extent, it still cannot meet the requirements, and the mechanical properties and high temperature resistance of the coatings are not very good. Summary of the invention:
[0004] The technical problem to be solved by the present invention is to provide a method for preparing a water-based epoxy-modified silicone high-temperature resistant anti-corrosion coating in view of the deficiencies in the prior art. The coating prepared by this method not only has good anti-corrosion performance, but also has excellent high-temperature resistance and good mechanical properties.
[0005] In order to solve the above technical problems, the technical solution adopted by the present invention is as follows:
[0006] A method for preparing a water-based epoxy-modified organosilicon high temperature resistant anticorrosive coating comprises the following steps:
[0007] (1) adding acidified water dropwise to an alkoxysilane monomer to react, thereby obtaining an organosilicon prepolymer;
[0008] (2) mixing a bisphenol A epoxy resin, a solvent and the organosilicon prepolymer obtained in step (1), heating, adding a catalyst, and reacting under constant temperature reflux, cooling after a period of reaction, then adding an emulsifier solution, and continuing the reaction at a constant temperature, and after the reaction is completed, cooling the reaction solution to room temperature and adding a pH adjuster to adjust the pH of the system to 7-8, thereby obtaining a water-based epoxy-modified organosilicon emulsion;
[0009] (3) Add water-based epoxy-modified silicone emulsion, deionized water, water-based defoaming agent, water-based dispersant, water-based bentonite, modified zinc phosphate anti-rust powder, wood biochar, ZIF nanosheets, glass powder, copper chrome black, barium sulfate, mica powder, film-forming aid, water-based flash rust inhibitor, and associative polyurethane thickener into a mixer, mix, and grind to a fineness of ≤30 μm to obtain a water-based epoxy-modified silicone high temperature resistant anticorrosive coating.
[0010] As a preferred embodiment of the above technical solution, in step (1), the acidified water is prepared by mixing a catalyst and deionized water, the catalyst is one of hydrochloric acid, sulfuric acid, and nitric acid, the added amount of the catalyst is 0.2-1wt% of the mass of the alkoxysilane monomer, and the added amount of the deionized water is 10-50wt% of the mass of the alkoxysilane monomer; the reaction temperature is 60-70°C, the dripping time of the acidified water is 3-5h, and the reaction is kept warm for 1-2h after the dripping is completed.
[0011] As a preferred embodiment of the above technical solution, in step (2), the model of the bisphenol A epoxy resin is one or more of E41, E33, E20, and E12; the solvent is a mixture of one or more of xylene, trimethylol, n-butanol, propylene glycol methyl ether, and cyclohexanone, and the amount of the solvent is 20-30wt% of the total amount of the bisphenol A epoxy resin and the silicone prepolymer.
[0012] As a preferred embodiment of the above technical solution, in step (2), the emulsifier solution is a mixed aqueous solution of alkylphenol polyoxyethylene ether and sodium dodecyl sulfonate, in which the mass concentrations of alkylphenol polyoxyethylene ether and sodium dodecyl sulfonate are 3-6wt% and 3-6wt%, respectively; the catalyst is aluminum acetylacetonate, and its added amount is 0.2-0.3wt% of the total amount of bisphenol A type epoxy resin and silicone prepolymer; the pH regulator is a mixture of one or more of dimethylethanolamine, triethylamine and ammonia water; and the percentage of the epoxy resin in the epoxy-silicone resin is 10-15wt%.
[0013] As a preferred embodiment of the above technical solution, in step (2), the temperature of the constant temperature reflux reaction is 200-220°C and the time is 6-8h; the temperature of the insulation reaction is 70-80°C and the time is 1-2h.
[0014] As a preferred embodiment of the above technical solution, in step (3), the modified zinc phosphate anti-rust powder is one or a mixture of strontium-modified zinc phosphate and barium-modified zinc phosphate.
[0015] As a preferred embodiment of the above technical solution, in step (3), the amount of each component used, by mass percentage, is 40-50wt% aqueous epoxy modified silicone emulsion, 15-20wt% deionized water, 0.1-0.2wt% aqueous defoamer, 1-2wt% aqueous dispersant, 2-4wt% aqueous bentonite, 4-6wt% modified zinc phosphate anti-rust powder, 5-10wt% glass powder, 5-10wt% copper chrome black, 3-4wt% barium sulfate, 3-4wt% mica powder, 2-3wt% film-forming aid, 0.3-0.5wt% flash rust inhibitor, 1-2wt% associative polyurethane thickener, 2-3wt% wood biochar, and 2-3wt% ZIF nanosheets.
[0016] As a preferred embodiment of the above technical solution, in step (3), the method for preparing the wood biochar is: drying the pine sawdust and placing it in a muffle furnace, heating it to 680-720°C at a rate of 3-5°C / min, and calcining it for 1-2h to obtain the biochar.
[0017] As a preferred embodiment of the above technical solution, in step (3), the preparation method of ZIF nanosheets is to dissolve zinc nitrate hexahydrate and 2-methylimidazole in deionized water, stir and hydrolyze at room temperature, then centrifuge, wash and dry the precipitate obtained by centrifugation.
[0018] As a preferred embodiment of the above technical solution, the molar ratio of zinc nitrate hexahydrate to 2-methylimidazole is 0.1:1; the rotation speed of the stirring at room temperature is 500-800 rpm, and the time is 24 hours.
[0019] In the present invention, the alkoxysilane monomer is a mixture of one or more of monomethyltriethoxysilane, dimethyldiethoxysilane and monophenyltriethoxysilane; the aqueous dispersant, the aqueous defoamer, the film-forming aid and the flash rust inhibitor are all additives commonly used in the art, which will not be described in detail here.
[0020] Due to the adoption of the above technical solution, the present invention has the following beneficial effects:
[0021] The present invention adopts an emulsification process to prepare a water-based epoxy-modified silicone emulsion, which greatly reduces the emission of VOCs during the production and construction process, is environmentally friendly and pollution-free, and the silicone resin modified by the epoxy group not only has excellent high temperature resistance and electrical insulation properties, but also greatly improves the flexibility of the coating and the adhesion to the substrate; the addition of modified zinc phosphate anti-rust powder, glass powder and copper chrome black can further improve the hardness, scratch resistance, chemical resistance, heat resistance and outdoor weather resistance of the coating; the coating is particularly suitable for long-term protection of metals or other materials working in high temperature and high corrosion environments.
[0022] The present invention also adds a certain amount of wood biochar and ZIF nanosheets to the coating. The addition of wood biochar can play a certain barrier role on the one hand, and on the other hand, the addition of wood biochar can provide additional electrical connection, thereby effectively triggering the self-corrosion of modified zinc phosphate anti-rust powder in the presence of electrolyte. The self-corrosion product can be used as a filling material to produce a better barrier effect, thereby improving the anti-corrosion performance of the coating; and the ZIF nanosheets play an obvious blocking role in the coating film, making the diffusion path of the corrosive medium tortuous, thereby improving the anti-corrosion performance of the coating film. Specific implementation method:
[0023] In order to better understand the present invention, the present invention is further described below by way of examples. The examples are only used to explain the present invention and will not constitute any limitation to the present invention.
[0024] Example 1
[0025] (1) 0.75 g of hydrochloric acid and 22.5 g of deionized water were mixed and stirred to prepare acidified water, and the acidified water was added dropwise to a mixed monomer consisting of 50 g of monomethyltriethoxysilane, 50 g of dimethyldiethoxysilane, and 50 g of monophenyltriethoxysilane. The acidified water was added dropwise within 3 hours. After the addition was completed, the reaction was carried out at 65° C. for 1 hour to prepare a silicone prepolymer;
[0026] (2) 100 g of xylene, 50 g of n-butanol, and 50 g of cyclohexanone are added to a reactor, and then 150 g of epoxy resin E41 and 450 g of the silicone prepolymer prepared in step (1) are added while stirring, and the mixture is heated to 210° C., 1.5 g of aluminum acetylacetonate is added under condensation reflux, and the mixture is refluxed at a constant temperature for 6 h. The mixture is then cooled to 70° C., and a mixed aqueous solution consisting of 10 g of alkylphenol polyoxyethylene ether, 10 g of sodium dodecyl sulfate, and 180 g of deionized water is added. The controller sets the dropping time to 1 h. After the dropping is completed, the reaction is continued at the temperature for 1 h. After the reaction is completed, the reaction solution is cooled to room temperature and dimethylethanolamine is added dropwise to adjust the pH value of the system to 7-8 to obtain a water-based epoxy-modified silicone emulsion;
[0027] (3) 30 g of pine sawdust was dried and placed in a muffle furnace, heated to 700 °C at a rate of 3 °C / min, and calcined for 1 h to obtain wood biochar; 0.4 mmol of zinc nitrate hexahydrate and 4 mmol of 2-methylimidazole were dissolved in 50 ml of deionized water, stirred and hydrolyzed at room temperature and 500 rpm for 24 h, and then centrifuged at 10,000 rpm for 30 min. The precipitate obtained by centrifugation was washed and dried to obtain ZIF nanosheets;
[0028] (4) 500 g of water-based epoxy-modified silicone emulsion, 200 g of deionized water, 1 g of water-based defoamer, 20 g of water-based dispersant, 3 g of water-based bentonite, 60 g of strontium-modified zinc phosphate anti-rust powder, 30 g of wood biochar, 30 g of ZIF nanosheets, 80 g of glass powder, 80 g of copper chrome black, 40 g of barium sulfate, 40 g of mica powder, 30 g of film-forming aid, 5 g of flash rust inhibitor, and 13 g of associative polyurethane thickener were added to a mixer, mixed, and ground to a fineness of ≤30 μm to obtain a water-based epoxy-modified silicone high temperature resistant anticorrosive coating.
[0029] Example 2
[0030] (1) 0.75 g of sulfuric acid and 22.5 g of deionized water were mixed and stirred to prepare acidified water, and the acidified water was added dropwise to a mixed monomer consisting of 50 g of monomethyltriethoxysilane, 50 g of dimethyldiethoxysilane, and 50 g of monophenyltriethoxysilane. The acidified water was added dropwise within 5 hours. After the addition was completed, the reaction was carried out at 70° C. for 1 hour to prepare a silicone prepolymer;
[0031] (2) 100 g of trimethylbenzene, 50 g of propylene glycol methyl ether, and 50 g of cyclohexanone are added to a reactor, and then 150 g of epoxy resin E41 and 450 g of the silicone prepolymer obtained in step (1) are added while stirring, and the mixture is heated to 220° C., 1.5 g of aluminum acetylacetonate is added under condensation reflux, and the mixture is refluxed at a constant temperature for 6 h. The mixture is then cooled to 80° C., and a mixed aqueous solution consisting of 10 g of alkylphenol polyoxyethylene ether, 10 g of sodium dodecyl sulfate, and 180 g of deionized water is added. The controller controls the addition time to be 0.5 h. After the addition is completed, the reaction is continued at the temperature for 2 h. After the reaction is completed, the reaction solution is cooled to room temperature and triethylamine is added dropwise to adjust the pH value of the system to 7-8 to obtain a water-based epoxy-modified silicone emulsion;
[0032] (3) 30 g of pine sawdust was dried and placed in a muffle furnace, heated to 700 °C at a rate of 5 °C / min, and calcined for 2 h to obtain wood biochar; 0.4 mmol of zinc nitrate hexahydrate and 4 mmol of 2-methylimidazole were dissolved in 50 ml of deionized water, stirred and hydrolyzed at room temperature and 800 rpm for 24 h, and then centrifuged at 10,000 rpm for 30 min. The precipitate obtained by centrifugation was washed and dried to obtain ZIF nanosheets;
[0033] (4) 500 g of water-based epoxy-modified silicone emulsion, 200 g of deionized water, 1 g of water-based defoamer, 20 g of water-based dispersant, 3 g of water-based bentonite, 60 g of barium-modified zinc phosphate anti-rust powder, 30 g of wood biochar, 30 g of ZIF nanosheets, 80 g of glass powder, 80 g of copper chrome black, 40 g of barium sulfate, 40 g of mica powder, 30 g of film-forming aid, 5 g of flash rust inhibitor, and 13 g of associative polyurethane thickener were added to a mixer, mixed, and ground to a fineness of ≤30 μm to obtain a water-based epoxy-modified silicone high temperature resistant anticorrosive coating.
[0034] Example 3
[0035] (1) 0.75 g of nitric acid and 22.5 g of deionized water were mixed and stirred to prepare acidified water, and the acidified water was added dropwise to a mixed monomer consisting of 50 g of monomethyltriethoxysilane, 50 g of dimethyldiethoxysilane, and 50 g of monophenyltriethoxysilane. The acidified water was added dropwise within 4 hours. After the addition was completed, the reaction was carried out at 65° C. for 2 hours to prepare a silicone prepolymer;
[0036] (2) 100 g of xylene, 50 g of propylene glycol methyl ether, and 50 g of cyclohexanone are added to a reactor, and then 150 g of epoxy resin E41 and 450 g of the silicone prepolymer prepared in step (1) are added while stirring, and the mixture is heated to 210° C., 1.5 g of aluminum acetylacetonate is added under condensation reflux, and the mixture is refluxed at a constant temperature for 7 h, and then the temperature is lowered to 75° C., and a mixed aqueous solution consisting of 10 g of alkylphenol polyoxyethylene ether, 10 g of sodium dodecyl sulfate, and 180 g of deionized water is added, and the controller controls the dropping time to be 1 h. After the dropping is completed, the reaction is continued at the temperature for 2 h. After the reaction is completed, the reaction solution is cooled to room temperature and ammonia water is added dropwise to adjust the pH of the system to 7-8 to obtain a water-based epoxy-modified silicone emulsion;
[0037] (3) 30 g of pine sawdust was dried and placed in a muffle furnace, heated to 700 °C at a rate of 4 °C / min, and calcined for 1 h to obtain wood biochar; 0.4 mmol of zinc nitrate hexahydrate and 4 mmol of 2-methylimidazole were dissolved in 50 ml of deionized water, stirred and hydrolyzed at room temperature and 600 rpm for 24 h, and then centrifuged at 10,000 rpm for 30 min. The precipitate obtained by centrifugation was washed and dried to obtain ZIF nanosheets;
[0038] (4) 500 g of water-based epoxy-modified silicone emulsion, 200 g of deionized water, 1 g of water-based defoamer, 20 g of water-based dispersant, 3 g of water-based bentonite, 60 g of strontium-modified zinc phosphate anti-rust powder, barium-modified zinc phosphate anti-rust powder, 30 g of wood biochar, 30 g of ZIF nanosheets, 80 g of glass powder, 80 g of copper chrome black, 40 g of barium sulfate, 40 g of mica powder, 30 g of film-forming aid, 5 g of flash rust inhibitor, and 13 g of associative polyurethane thickener were added to a mixer, mixed, and ground to a fineness of ≤30 μm to obtain a water-based epoxy-modified silicone high temperature resistant anticorrosive coating.
[0039] Example 4
[0040] (1) 0.75 g of hydrochloric acid and 22.5 g of deionized water were mixed and stirred to prepare acidified water, and the acidified water was added dropwise to a mixed monomer consisting of 50 g of monomethyltriethoxysilane, 50 g of dimethyldiethoxysilane, and 50 g of monophenyltriethoxysilane. The acidified water was added dropwise within 4.5 hours. After the addition was completed, the reaction was carried out at 65° C. for 1 hour to prepare a silicone prepolymer;
[0041] (2) 100 g of trimethylbenzene, 50 g of n-butanol and 50 g of cyclohexanone are added to a reactor, and then 150 g of epoxy resin E41 and 450 g of the organosilicon prepolymer prepared in step (1) are added while stirring, and the mixture is heated to 210° C., 1.5 g of aluminum acetylacetonate is added under condensation reflux, and the mixture is refluxed at a constant temperature for 7 h, and then the temperature is lowered to 75° C., and a mixed aqueous solution consisting of 10 g of alkylphenol polyoxyethylene ether, 10 g of sodium dodecyl sulfate and 180 g of deionized water is added, and the controller sets the dropping time to 1 h. After the dropping is completed, the reaction is continued at the temperature for 2 h. After the reaction is completed, the reaction solution is cooled to room temperature and ammonia water is added dropwise to adjust the pH value of the system to 7-8 to obtain a water-based epoxy-modified organosilicon emulsion;
[0042] (3) 30 g of pine sawdust was dried and placed in a muffle furnace, heated to 700 °C at a rate of 4 °C / min, and calcined for 1.5 h to obtain wood biochar; 0.4 mmol of zinc nitrate hexahydrate and 4 mmol of 2-methylimidazole were dissolved in 50 ml of deionized water, stirred and hydrolyzed at room temperature and 700 rpm for 24 h, and then centrifuged at 10,000 rpm for 30 min. The precipitate obtained by centrifugation was washed and dried to obtain ZIF nanosheets;
[0043] (4) 500 g of water-based epoxy-modified silicone emulsion, 200 g of deionized water, 1 g of water-based defoamer, 20 g of water-based dispersant, 3 g of water-based bentonite, 60 g of strontium-modified zinc phosphate anti-rust powder, barium-modified zinc phosphate anti-rust powder, 30 g of wood biochar, 30 g of ZIF nanosheets, 80 g of glass powder, 80 g of copper chrome black, 40 g of barium sulfate, 40 g of mica powder, 30 g of film-forming aid, 5 g of flash rust inhibitor, and 13 g of associative polyurethane thickener were added to a mixer, mixed, and ground to a fineness of ≤30 μm to obtain a water-based epoxy-modified silicone high temperature resistant anticorrosive coating.
[0044] Comparative Example 1
[0045] No wood biochar is added to the waterborne epoxy-modified silicone high temperature resistant anticorrosive coating, and other conditions are the same as those in Example 4.
[0046] Comparative Example 2
[0047] No ZIF nanosheets are added to the waterborne epoxy-modified silicone high temperature resistant anticorrosion coating, and other conditions are the same as those in Example 4.
[0048] The coatings prepared in the above embodiments and comparative examples were coated on the surface of the sample to obtain a paint film with a thickness of 120 μm, and cured at 160° C. for 20 min to obtain a coating film. The coating film was then tested for performance. The test results are shown in Table 1.
[0049] Table 1
[0050]
[0051]
[0052] It can be seen from the above test results that the coating prepared by the present invention not only has good anti-corrosion performance, but also has good mechanical properties. The synergy between the modified zinc phosphate anti-rust powder, wood biochar and ZIF nanosheets effectively improves the anti-corrosion performance of the coating.
[0053] In addition, it should be understood that after reading the contents of the present invention, those skilled in the art may make various changes or modifications to the present invention, and these equivalent forms also fall within the scope defined by the claims attached to this application.
Claims
1. A method for preparing a water-based epoxy-modified silicone high temperature resistant anticorrosive coating, characterized in that: The following steps are involved: (1) Acidified water is added dropwise to an alkoxysilane monomer to react, thereby obtaining an organosilicon prepolymer; the acidified water is prepared by mixing a catalyst and deionized water, the catalyst is one of hydrochloric acid, sulfuric acid, and nitric acid, the amount of the catalyst added is 0.2-1wt% of the mass of the alkoxysilane monomer, and the amount of the deionized water added is 10-50wt% of the mass of the alkoxysilane monomer; the reaction temperature is 60-70°C, the acidified water is added dropwise for 3-5h, and after the addition is completed, the reaction is kept warm for 1-2h; (2) mixing bisphenol A epoxy resin, solvent and the organosilicon prepolymer obtained in step (1), heating, adding a catalyst, and reacting under constant temperature reflux. After reacting for a period of time, cooling, adding an emulsifier solution, and continuing the reaction at a constant temperature. After the reaction is completed, cooling the reaction solution to room temperature and adding a pH adjuster to adjust the pH of the system to 7-8, thereby obtaining a water-based epoxy-modified organosilicon emulsion; (3) Add water-based epoxy-modified silicone emulsion, deionized water, water-based defoamer, water-based dispersant, water-based bentonite, modified zinc phosphate anti-rust powder, wood biochar, ZIF nanosheets, glass powder, copper chrome black, barium sulfate, mica powder, film-forming aid, flash rust inhibitor, and associative polyurethane thickener into a mixer, mix, and grind to a fineness of ≤30 μm to obtain a water-based epoxy-modified silicone high temperature resistant anticorrosive coating; The amount of each component is calculated by mass percentage, which is 40-50wt% of water-based epoxy modified silicone emulsion, 15-20wt% of deionized water, 0.1-0.2wt% of water-based defoamer, 1-2wt% of water-based dispersant, 2-4wt% of water-based bentonite, 4-6wt% of modified zinc phosphate anti-rust powder, 5-10wt% of glass powder, 5-10 wt% of copper chrome black, 3-4wt% of barium sulfate, 3-4wt% of mica powder, 2-3wt% of film-forming aid, 0.3-0.5wt% of water-based flash rust inhibitor, 1-2wt% of associative polyurethane thickener, 2-3wt% of wood biochar, and 2-3wt% of ZIF nanosheets; The emulsifier solution is a mixed aqueous solution of alkylphenol polyoxyethylene ether and sodium dodecyl sulfonate, in which the mass concentrations of alkylphenol polyoxyethylene ether and sodium dodecyl sulfonate are 3-6wt% and 3-6wt% respectively; the catalyst is aluminum acetylacetonate, and its added amount is 0.2-0.3wt% of the total amount of bisphenol A epoxy resin and silicone prepolymer; the pH adjuster is a mixture of one or more of dimethylethanolamine, triethylamine, and ammonia water; the percentage of the epoxy resin in the epoxy-silicone resin is 10-15wt%.
2. The method for preparing a water-based epoxy-modified silicone high temperature resistant anticorrosive coating according to claim 1, characterized in that: In step (2), the model of the bisphenol A epoxy resin is one or more of E41, E33, E20, and E12; the solvent is a mixture of one or more of xylene, trimethylol, n-butanol, propylene glycol methyl ether, and cyclohexanone, and the amount of the solvent used is 20-35wt% of the total amount of the bisphenol A epoxy resin and the silicone prepolymer.
3. The method for preparing a water-based epoxy-modified silicone high temperature resistant anticorrosive coating according to claim 1, characterized in that: In step (2), the temperature of the constant temperature reflux reaction is 200-220°C, and the time is 6-8h; the temperature of the insulation reaction is 70-80°C, and the time is 1-2h.
4. The method for preparing a water-based epoxy-modified silicone high temperature resistant anticorrosive coating according to claim 1, characterized in that: In step (3), the modified zinc phosphate anti-rust powder is one or a mixture of strontium-modified zinc phosphate and barium-modified zinc phosphate.
5. The method for preparing a water-based epoxy-modified silicone high temperature resistant anticorrosive coating according to claim 1, characterized in that: In step (3), the method for preparing the wood biochar is as follows: drying the pine sawdust and placing it in a muffle furnace, heating it to 680-720°C at a rate of 3-5°C / min, and calcining it for 1-2h to obtain the biochar.
6. The method for preparing a water-based epoxy-modified silicone high temperature resistant anticorrosive coating according to claim 1, characterized in that: In step (3), the preparation method of ZIF nanosheets is to dissolve zinc nitrate hexahydrate and 2-methylimidazole in deionized water, stir and hydrolyze at room temperature, then centrifuge, wash and dry the precipitate obtained by centrifugation.
7. The method for preparing a water-based epoxy-modified silicone high temperature resistant anticorrosive coating according to claim 6, characterized in that: The molar ratio of zinc nitrate hexahydrate to 2-methylimidazole is 0.1:1; the stirring speed at room temperature is 500-800 rpm, and the stirring time is 24 hours.
Citation Information
Patent Citations
Method for preparing aqueous organic silicone emulsion with phase reversion method
CN108641097A
Water-based brake disc coating and preparation method thereof
CN114231131A